1989
DOI: 10.1002/chin.198950007
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Crystal Structure of YbPS4.

Abstract: ChemInform Abstract The novel title compound is prepared by solid-phase reaction at 800 rc C in evacuated quartz ampoules (1.33 Pa) starting from Yb(PO3)3 and Yb2S3. It belongs to the space group I 41/acd with Z=16. The structure is characterized by slightly distorted PS4 tetrahedra. The Yb cations are distributed around them that way that the metal adopts an eightfold coordination to sulfur. The YbS8 polyhedra are connected by sharing edges and corners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…For TmPS 4 , Huang et al [21] arrived at lattice parameters of a = 10.5962 (2), c = 18.881(1) Å, and Wibbelmann et al [5] described a brownish color (contrary to the pale-yellow color of the compound presented here). For YbPS 4 , different lattice parameters were reported in the literature, namely a = 10.571(1), c = 18.817(2) Å in a study by Le Rolland et al [8], which are significantly smaller than the powder lattice parameters a = 10.664 (2), c = 18.989(4) Å reported by Palkina et al [6,22]. Further, Le Rolland et al described the color of YbPS 4 to be black, while we will show that the color is reddish brown [8].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…For TmPS 4 , Huang et al [21] arrived at lattice parameters of a = 10.5962 (2), c = 18.881(1) Å, and Wibbelmann et al [5] described a brownish color (contrary to the pale-yellow color of the compound presented here). For YbPS 4 , different lattice parameters were reported in the literature, namely a = 10.571(1), c = 18.817(2) Å in a study by Le Rolland et al [8], which are significantly smaller than the powder lattice parameters a = 10.664 (2), c = 18.989(4) Å reported by Palkina et al [6,22]. Further, Le Rolland et al described the color of YbPS 4 to be black, while we will show that the color is reddish brown [8].…”
Section: Introductionmentioning
confidence: 79%
“…During our investigations on lanthanide orthothiophosphates we noticed that TmPS 4 and YbPS 4 have not been synthesized as single crystals [6], even though their lattice parameters were reported from X-ray powder diffraction experiments several times [8,[20][21][22]. For TmPS 4 , Huang et al [21] arrived at lattice parameters of a = 10.5962 (2), c = 18.881(1) Å, and Wibbelmann et al [5] described a brownish color (contrary to the pale-yellow color of the compound presented here).…”
Section: Introductionmentioning
confidence: 99%
“…Two different types of structural arrangements are known for these compounds that can generally be classified into seven structure types denoted by roman numerals: cyclotetraphosphates M I REP 4 O 12 with a ring structure formed by four PO 4 tetrahedra that are joined by bridging O atoms, and polyphosphates M I RE(PO 3 ) 4 consisting of helical ribbons formed by corner-sharing PO 4 tetrahedra (Jouadi et al, 2003;Ettis et al, 2003). Previous structure analyses have shown that rare earth polyphosphates with the general formula M I RE(PO 3 ) 4 crystallize in two crystal systems: orthorhombic with space group C222 1 (type VII) (M I = NH 4 , RE = Y) (Bagieu-Beucher & Guitel, 1988) or space group Pbna (M I = Li, M III = Ga) (Palkina et al, 1981a), and monoclinic with space groups C2/c (Koizumi, 1976;Hamady et al, 1995;Mokhtar et al, 1984) (type I), P2 1 /n (Palkina et al, 1981b;Maksimova et al, 1978) (types II, IV and V), P2 1 /c (Ben Hassen et al, 1982;Dogo et al, 1980) or P2 1 (Yong-Hua et al, 1983;Palkina, Maksimova, Kuznetsova & Chibiskova, 1978). All these materials have been intensively studied for their electric and optical properties, and some of them have applications in catalysis.…”
Section: Commentmentioning
confidence: 99%
“…One can notice that in the three well investigated types of acidic long-chain polyphosphates the associated cation polyhedra are isolated. Palkina et al [56] tried to explain this behavior which is rather unusual in condensed phosphate arrangements. According to these authors, the linkage of the anionic chains by H-bonds reduces their flexibility and hinders the possibility of forming aggrega tes of associated cation polyhedra, whereas in simple polyphosphates where the flexibility of chains is not violated by the presence of H-bonds the associa tion of the MO n polyhedra is possible with the formation of either finite or infinite aggregates depending on the cation sizes and on their oxygen coordinations.…”
Section: Acidic Anion Network In Long-chain Polyphosphatesmentioning
confidence: 98%